RANCANGAN PENYUSUNAN LAPORAN KEUANGAN BERBASIS MICROSOFT ACCES BERDASARKAN SAK EMKM PADA UKM DEWI PROL TAPE - Admaja, Fitroh Marga Mila Aria; Oktaviana, Ulfi Kartika (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Dewi Prol Tape is one of Micro Small and Medium Entities which already have Micro Small Business Permit (IUMK) and turnover which increase every year. With administrative completeness as well as a good turnover increase, in the preparation of its financial statements are still not compiled well and in accordance with SAK EMKM. The preparation of the required financial statements is software-based for easy use by the UKM. Software used is microsoft acces where in operation does not require high accounting skills and does not require the cost to get it.So with that background this research is done with the title: